Strategies of Health Workers in Tackling Stunting in Rural Areas during the Covid-19 Pandemic - Ni Putu Wiwik Oktaviani; Ni Wayan Trisnadewi; I Made Sudarma Adiputra (Indonesian Journal of Global Health Research, 2022)
The current Covid-19 vaccination has reached most people throughout Indonesia. The main focus of this spectrum is on handling the Covid-19 pandemic through the provision of vaccines in Indonesia. The pandemic's impact is indisputably clear, especially in the Stunting Management Programs, which are likely not optimal and require a viable strategy in handling it. Objective: This study aims to identify the strategy of health workers in tackling stunting in rural areas during the Covid-19 Pandemic. Method: This study employs a quantitative descriptive design where the population involved are health workers holding nutrition programs from health centres in rural areas in the province of Bali. The sampling technique in this study utilizes a non-probability sampling technique, namely purposive sampling of 34 respondents. Afterwards, data collection was done online, with the inclusion criteria for health workers working as nutrition program holders and community health centres in rural areas. This study indicates that 55.90% of health workers are not well-performing at dealing with stunting during the pandemic, while 44.10% of them show positive performance. Therefore, prevention of stunting by health workers during a pandemic is one of the indicators of whether stunting is in a high or low incidence.